Adjusting the role of hydroxychloroquine with or without azithromycin in patients with COVID-19 - V. A. Otdelenov; Yu. Yu. Kiselev; K. B. Mirzaev; A. V. Matveev; D. A. Sychev (Качественная клиническая практика, 2020)
Taking recent publications into account, one should consider avoiding routine use of hydroxychloroquine, especially if combined with azithromycin, for COVID-19. Such treatment may be associated with the increased risk for hospital mortality and QT prolongation, while there is no documented effectiveness regarding SARS-CoV-2 clearance and outcomes. This treatment may be considered in individual cases, provided potential benefit and risks are carefully weighted, and safety monitoring is enhanced. Hydroxychloroquine safety in outpatients with COVID-19 is poorly studied and risks are increased by challenges in monitoring QT and electrolytes, hence hydroxychloroquine cannot be considered as first line treatment in outpatient settings. Such use of hydroxychloroquine is not recommended if clinical, instrumental, and laboratory monitoring are not in place.